Evaluation of Project Work in a Public Service Building in East Java - Andhika Dwi Kurniawan; Arief Rachmansyah; Yatnanta Padma Devia (Department of Civil Engineering, Faculty of Engineering, Universitas Brawijaya, 2023)
In the process of implementing a project, few people find projects that go according to plan. In general, there are projects that are behind schedule, both in terms of time and schedule, but there are also projects that experience acceleration from the originally planned schedule. Project delay is a problem that arises as a result of unplanned construction implementation. Damage to the state due to additional costs and delays is one of the impacts of project delays. The purpose of this research is to track project implementation, identify factors that cause delays, calculate the cost of delays that occur, find root causes and suggest alternative solutions that can be used to anticipate project delays. Monitoring and evaluating delays require an approach that includes the use of Microsoft Project Tracking, Fishbone Charts, and Root Cause Analysis. Alternative methods are used to track performance and analyze delays in public service building projects. The results showed a lack of understanding of human resources in terms of planning/evaluating existing plans, lack of training programs related to the field of work being handled, and poor schedule planning causing a lack of lightning rods, installation in the main building, lighting in changing rooms, grounding systems, central duct/airline, less power cables than needed and original water source using PAM water converted into deep pumping wells.